TYPES OF POWER IN INTERTEXTUALITY: SIR KEN ROBINSON'S TED TALK 'DO SCHOOLS KILL CREATIVITY?' AS A SAMPLE - SARKISIAN, ARAXI KRIKOR THOMAS; AL-RUBAI'I, ALYA M. H. AHMED (Journal of Duhok University, 2021)
This study attempted to investigate the use of intertextuality as a source of power in a TED talk sample, viz., Sir Ken Robinson's 'Do Schools Kill Creativity?' within the framework of Critical Discourse Analysis (CDA). This paper followed a qualitative paradigm in analyzing the sample data. Accordingly, an eclectic model was devised, integrating Gee's (2014a, 2014b) model of intertextual analysis and French and Raven's (1959) model of the bases of social psychological power. The application of this model to the selected data has yielded some conclusions, the most salient of which is that intertextuality is important in TED talks as it is used to show implicit meanings to exercise two types of power: expert power and referent power. Accordingly, it is recommended to consider power relations and the exercise of power when conducting any intertextual analysis within the framework of CDA.